2017
DOI: 10.1038/nprot.2017.075
|View full text |Cite
|
Sign up to set email alerts
|

Meganuclease-assisted generation of stable transgenics in the sea anemone Nematostella vectensis

Abstract: The sea anemone Nematostella vectensis is a model system used by a rapidly growing research community for comparative genomics, developmental biology and ecology. Here, we describe a microinjection procedure for creating stable transgenic lines in Nematostella based on meganuclease (I-SceI)-assisted integration of a transgenic cassette into the genome. The procedure describes the preparation of the reagents, microinjection of the transgenesis vector and the husbandry of transgenic animals. The microinjection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…While identifying sleep in jellyfish and molluscs opens the door for studies for sleep function, rhythmic circadian behavior or gene expression has been identified in many other systems that have not been analysed for sleep (Joiner, 2016). For example, the starlet sea anemone Nematostella vectensis has robust circadian behavioral and molecular rhythms, a simplified and transparent nervous system, and is amenable to transgenic manipulation (Hendricks et al, 2012;Peres et al, 2014;Oren et al, 2015;Renfer and Technau, 2017). Molecular circadian rhythms have also been identified in the tunicate sea squirt Ciona intestinalis that are accompanied by circadian-dependent regulation of oxygen consumption (Minamoto et al, 2010).…”
Section: Potential Applications For Gastropod and Cephalopod Models Imentioning
confidence: 99%
“…While identifying sleep in jellyfish and molluscs opens the door for studies for sleep function, rhythmic circadian behavior or gene expression has been identified in many other systems that have not been analysed for sleep (Joiner, 2016). For example, the starlet sea anemone Nematostella vectensis has robust circadian behavioral and molecular rhythms, a simplified and transparent nervous system, and is amenable to transgenic manipulation (Hendricks et al, 2012;Peres et al, 2014;Oren et al, 2015;Renfer and Technau, 2017). Molecular circadian rhythms have also been identified in the tunicate sea squirt Ciona intestinalis that are accompanied by circadian-dependent regulation of oxygen consumption (Minamoto et al, 2010).…”
Section: Potential Applications For Gastropod and Cephalopod Models Imentioning
confidence: 99%
“…The NvPOU4::memGFP transgenic reporter line was generated by meganuclease-mediated transgenesis as described by (Renfer and Technau, 2017 (2)::mOrange line has been described in (Richards and Rentzsch, 2014), NvElav1::mOrange in (Nakanishi et al, 2012), NvNCol3::mOrange in (Sunagar et al, 2018) and NvFoxQ2d::mOrange in (Busengdal and Rentzsch, 2017). An overview of the crosses are provided in Table S4.…”
Section: Generation Of Transgenic Linesmentioning
confidence: 99%
“…Since the early 2000s, Nematostella researchers have developed several protocols including maintenance and spawning procedures 14,15 , isolation of protein and nucleic acids 16 , in situ hybridization 17, ,, 18 , microinjection and morpholino-based gene knockdown 19 , meganuclease-mediated transgenesis 20 and CRISPR/Cas9-based gene editing 21 . Recently, we developed a gene knockdown method based on microinjection of gene-specific shRNA into Nematostella eggs (He et al, in press 2018).…”
Section: Introductionmentioning
confidence: 99%